Multifocal Tuberculous Osteomyelitis of Ribs with Active Pulmonary Infection - Venkatesh Elumalai; K. Krishnamoorthy; T. Joseph Pratheeban; E. Mathan; O. M. Rahman Shahul Hameed (Journal of Association of Pulmonologist of Tamil Nadu)
Skeletal tuberculosis (TB) is a type of extrapulmonary TB affecting bony structures. Surprisingly, rib involvement is rare, comprising only 0%–5% of bone TB cases. Multifocal tuberculous osteomyelitis of the rib is a very rare condition, affecting only 0.1% of individuals with TB. We present here the case of a 28-year-old male who is an accountant in a travel agency with no comorbidities presented with complaints of cough with expectoration and swelling over the left posterolateral chest wall for 3 months’ duration. Imaging by computed tomography and magnetic resonance imaging of the chest showed features of multifocal tuberculous osteomyelitis of ribs with active pulmonary TB. Pus was aspirated from chest wall swelling detected mycobacterium TB in Catridge based nucleic acid amplification test, and the patient was started on antitubercular therapy. This case emphasizes skeletal TB, despite being the prevalent form of extrapulmonary TB, and presents an intriguing aspect with rib involvement remaining a relatively rare phenomenon.